Essays on social interaction and market fragmentation in experimental finance - Wang, Yan (Nanyang Technological University, 2024)
In recent years, the fields of economics and finance have witnessed the emergence of intricate phenomena, most notably, social interaction and market fragmentation. The former, social interaction, signifies the information exchange between individuals, which directly influences trading behaviors. The first chapter delves into a particularly significant aspect of social interaction, the incentive to circulate rumors. On the other hand, market fragmentation describes a scenario where a singular market bifurcates into distinctive subsets or fragments, frequently a result of influences such as regulatory environments, advancements in technology, or shifting consumer preferences. These fragments often operate in a semi-independent manner, characterized by differential prices, products, or market dynamics. The second and third chapters navigate the impacts of an emergent trading venue, known as a “dark pool", within a fragmented market environment. In Chapter 1, we design an experiment to investigate the distinct incentives for spreading rumors between short-term and long-term rumormongers, as well as the beliefs of rumor-recipients concerning the information they receive. We find that short-term rumormongers are more likely to disclose private information truthfully, while long-term rumormongers display a propensity to deceive. Consequently, rumor-recipients tend to exhibit a greater degree of trust in the rumors conveyed by short-term rumormongers, while maintaining skepticism when evaluating rumors originating from their long-term counterparts. Moreover, trust between rumor-recipients and short-term rumormongers progressively strengthens over time. The incentive to tell the truth is notably more pronounced for short-term rumormongers participating in a continuous double auction compared to a call auction, which can be attributed to the enhanced transparency of market environment. In Chapter 2, we conduct an experiment to investigate the impact of dark trading on the incentive for acquiring costly information, market quality, and the overall welfare of traders within a virtual financial market. Our experimental framework incorporates either a lit market as a baseline scenario, or a dual-market system comprising both a lit market and a dark pool. Under conditions characterized by high precision in information, we find a positive correlation between dark trading and the motivation to acquire costly information. Moreover, our findings highlight a non-linear effect on information aggregation and price discovery. This non-linear relationship suggests that the full benefits of dark trading can be harnessed, provided that a carefully calibrated ceiling policy is implemented. In Chapter 3, we conduct an experiment to examine the impact of dark trading within the context of varying degrees of information dissemination. The channel through which dark trading influences market efficiency is contingent upon the distribution of fundamental information among investors. In scenarios where information is predominantly held by a select group of investors, potentially due to limited investor connectivity or insufficient media exposure, dark trading primarily affects market efficiency by diminishing the quality of asset prices. Notably, the decrease in price efficiency stemming from the introduction of a dark pool is not accompanied by a commensurate decline in allocative efficiency. Consequently, the profit disparity between informed and uninformed traders does not substantially widen as a result of dark trading.